IMPLEMENTASI METODE MIMICRY MEMORIZATION (MIM-MEM) DALAM MENINGKATKAN PENGUASAAN PEMBELAJARAN MUFRODAT DI KELAS V MDTA BANUN BANAT CIPULUS - kholil, Muhammad Kholil (Riyahuna: Jurnal Pendidikan Bahasa Arab, 2024)
The problem in this research is that students experience difficulty in memorizing Mufrodat due to the lack of media used in the learning process at MDTA Banun Banat Cipulus. The aim of this research is to determine the ability to memorize mufrodat skills using the MIM-MEM (Mimicry Memorization) media at MDTA Banun Banat Cipulus Purwakarta. This research uses quantitative experimental research methods with a one-group pretest-posttest design. Method Data collection used in this research was through observation, test questions, and interviews. Apart from that, data analysis in this research uses NGain calculations, normality tests and hypothesis tests. The samples taken in this research were 20 students from class V MDTA Banun Banat Cipulus Purwakarta. From the results of research on students' reading abilities through test questions, the pre-test average was 60.75 and the post-test average was 75.75. The results of the sig t-test calculation (2-tailed) were 0.000 > 0.005, indicating the influence of the application of MIM-MEM (Mimicry-Memorization) media. It can also be seen that the influence of this media is 1.64 in the strong category. This proves that there is a significant influence of Mimicry Memorization media on the Mufrodat Memorization learning model at MDTA Banun Banat Cipulus. Based on the results of the research and discussion, it can be concluded that the application of media using Mimicry Memorization in class V MDTA Banun Banat Cipulus students. The research results show 1). Students' tension decreased because they were more relaxed in using Card media. 2). Increasing students' ability to memorize mufrodat. 3). Mufrodat is easy to remember because there is also an image medium. So far the shortcomings of the MIM-MEM (Mimicry Memorization) method have not been discovered.